On the Chameleonic Behaviour of Cholesterol through a Fractal/Multifractal Model. (6th January 2020) - Tesloianu, Nicolae Dan; Ghizdovat, Vlad; Agop, Maricel; Rusu, Cristina; Cardoneanu, Anca
Abstract : An increasing number of studies are beginning to show that both low-density lipoprotein and high-density lipoprotein cholesterol can constitute risk factors for myocardial infarction. Such a behaviour has been called by experts in the field the "chameleonic effect" of cholesterol. In the present paper, a fractal/multifractal model for low-density lipoprotein and high-density lipoprotein cholesterol dynamics is proposed. In such a context, a fractal/multifractal tunneling effect for systems with spontaneous symmetry breaking is analyzed so that if the spontaneous symmetry breaking is assimilated to an inflammation (in the form of a specific scalar potential), then a coupling between two fractal/multifractal states can be observed. These two states, which have been associated to biological structures such as low-density lipoprotein and high-density lipoprotein, transfer their states through a fractal/multifractal tunneling effect. Moreover, in our opinion, the widely used notions of "good" and "bad" cholesterol must be redefined as two different states (low-density lipoprotein and high-density lipoprotein) of the same biological structure named "cholesterol." In our work, for the first time in the specialized literature, low-density lipoprotein and high-density lipoprotein have been regarded as two different states of the same biological structure (named "cholesterol"), such as in nuclear physics, the neutron and proton are two different states of the same particle named nucleon.